Blockchain-Enabled Pedagogical Frameworks for Financial Literacy Enhancement: A Systematic Review - Dhanda, Kunal (Journal of Research in Vocational Education, 2025)
This study examines how cloud computing can enhance financial literacy education through scalable and interactive e - learning solutions. Using a mixed - methods approach, the research evaluates both quantitative and qualitative impacts on student engagement, educational accessibility, and learning outcomes. Findings indicate that cloud - based tools significantly improve personalization and scalability, though challenges such as data privacy and infrastructure limitations remain. The study offers strategic recommendations for optimizing cloud - driven e - learning environments and outlines future research opportunities to further integrate AI and adaptive learning technologies.